Le Parc naturel urbain en Suisse : une utopie ? - Gérald Hess; Joëlle Salomon Cavin (VertigO, 2015)
This paper examines the city/nature relationship through the lens of the policy of natural parks in Switzerland. Using a philosophical approach of the idea of nature, it shows that the creation of the Swiss National Park was linked with an underlying opposition between human and nature. After the evolution of the legal framework in 2006, this dichotomy remains vivid in the city/nature relationship. Discussing the category of urban natural park, our proposition intends to exceed this dichotomy using philosophical concepts of phenomenoly and critical thought as elaborated by G. Böhme, A. Berque and V. Plumwood. Our proposal is thereby structured around the idea of nature in interiority relationship or in relation of identification with the city. Such approaches allow an integrative conception of nature and city. It implies, for the actors involved in defining the natural parks in Switzerland, a decentering allowing a less hostile view of the city.